Variation in climate and hydrological conditions in Southwest China during the mid-to-late Holocene, inferred from stalagmite multiple proxies - Li, Hua-Yan; Wu, Yao; Li, Ting-Yong; Duan, Rong; Wang, Hai-Bo; Cui, Jia-Hui; Chen, Chao-Jun; Jin, Yue; Xiang, Yue-Hua; Liu, Zi-Qi; Li, Jun-Yun (Palaeogeography, palaeoclimatology, palaeoecology, 2025)
Speleothem δ18O, δ13C, growth rate, Mg/Ca and Sr/Ca record varying environmental information due to their different influencing factors. Multiproxy analysis provides a deeper, multiangled interpretation of the palaeoclimate information recorded in speleothems. This work analyses the environmental information recorded by the δ18O, δ13C, growth rate, Mg/Ca and Sr/Ca ratios of multiple stalagmites, and other proxies of lake sediments in Southwest China during the mid-to-late Holocene. The results indicate that (1) the δ18O and δ13C values of stalagmite FL2 showed a gradually positive trend and were consistent with the decreasing pattern of precipitation affected by the Asian summer monsoon during 6.2-0.69 ka BP. (2) In the three periods of 6.2-4.2, 4.2-2.2 and 2.2-0.69 ka BP, the δ18O and δ13C values of stalagmite FL2 showed positive-negative-positive trends, respectively. Accordingly, the Mg/Ca ratios showed an increasing-decreasing-increasing trend, corresponding to the decreasing-increasing-decreasing variation characteristics of precipitation. The growth rate was sensitive to the increased precipitation from 4.2 to 2.2 ka BP. (3) The δ18O and δ13C values changed positively, and the Mg/Ca and Sr/Ca ratios increased when extreme climate events occurred (e.g. 5.5, 4.2, 2.8 and 1.0 ka event) in the mid-to-late Holocene. The multiple geochemical proxies of stalagmite FL2 corresponded well with the records in other stalagmites and lake sediments in Southwest China. (4) Principal component analysis (PCA) and power spectral analysis reveal that the δ18O values of stalagmite FL2 mainly respond to the changes in the Asian summer monsoon intensity at decadal to centennial scales and even longer. The δ13C values and Mg/Ca and Sr/Ca ratios mainly reflect decadal and multidecadal variability in regional precipitation.